Perception of women entrepreneurs to accessing bank credit - Touheda Yasmin Chowdhury; Aysa Yeasmin; Zobayer Ahmed (Journal of Global Entrepreneurship Research, 2018)
Women entrepreneurs play a substantial role in the sustainable economic development of various developed as well as developing countries in the world. In Bangladesh, the contribution of women entrepreneurs is still insignificant compared to other entrepreneurship due to a number of barriers to their financial inclusion. The current study tried to find out the problems faced with and the opinion of women entrepreneurs regarding the finance from commercial banks. The study used primary data from a sample survey, Key Informant Interview (KII) and in-depth interviews with the selected women entrepreneurs from Sylhet city of Bangladesh to meet the research objectives. Using Exploratory Factor Analysis (EFA), the study brings to life the fact that women entrepreneurs are reluctant to take the loan from banks because they have to face a number of problems there. Some of the major problems they faced are- collateral requirements, terms and conditions of bank loan, business characteristics and some other institution-specific problems to get access to bank finance. The findings of the study can aid the commercial banks in formulating their strategic decision about financing women entrepreneurs. In addition, this study indicates the way forward for the authoritative and supporting organizations of women entrepreneurs to formulate their action plans for the development of women entrepreneurship.
Keywords: 650; Women entrepreneurship; Bank financing; Entrepreneurship development; Bank loan; Bangladesh